2016
DOI: 10.1177/0192513x15578007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Gatekeeping

Abstract: Using data from the Fragile Families and Child Wellbeing Study (N = 3,605), the present study examined two aspects of maternal gatekeeping in relation to low-income predominantly nonresidential fathers' engagement with young children: facilitation and encouragement. The results showed that maternal encouragement when children were 3 years old was positively and longitudinally related to higher levels of paternal engagement with 5 year old children. However, maternal facilitation at age 3 was negatively associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 31 publications
1
7
0
2
Order By: Relevance
“…Maternal gatekeeping, a component of the coparenting relationship (Schoppe-Sullivan & Altenburger, 2019), reflects mothers' encouragement and discouragement of fathers' involvement in childrearing (Schoppe-Sullivan, Brown, Cannon, Mangelsdorf, & Sokolowski, 2008). Greater maternal gate-closing and less maternal gateopening are associated with lower father involvement in childrearing (Fagan & Cherson, 2017;Schoppe-Sullivan et al, 2008) and lower paternal parenting quality (Altenburger, Schoppe-Sullivan, & Kamp Dush, 2018).…”
Section: Family Relationshipsmentioning
confidence: 99%
“…Maternal gatekeeping, a component of the coparenting relationship (Schoppe-Sullivan & Altenburger, 2019), reflects mothers' encouragement and discouragement of fathers' involvement in childrearing (Schoppe-Sullivan, Brown, Cannon, Mangelsdorf, & Sokolowski, 2008). Greater maternal gate-closing and less maternal gateopening are associated with lower father involvement in childrearing (Fagan & Cherson, 2017;Schoppe-Sullivan et al, 2008) and lower paternal parenting quality (Altenburger, Schoppe-Sullivan, & Kamp Dush, 2018).…”
Section: Family Relationshipsmentioning
confidence: 99%
“…Some work has found that gate opening behaviors do predict increased father involvement, thereby promoting the father-child relationship and coparenting (Schoppe-Sullivan et al, 2008). Other work has found fathers' perceptions of greater maternal gate opening behaviors to enhance father involvement, but mothers' perceptions of greater maternal gate opening behaviors to be detrimental to father involvement (Fagan & Cherson, 2015). Thus, it appears that perceptions of gate opening may differ for mothers and fathers (Schoppe-Sullivan & Altenburger, 2018), and that how fathers perceive maternal behaviors may be critical for understanding the potential impact of maternal gatekeeping.…”
Section: Maternal Gatekeepingmentioning
confidence: 99%
“…One finding of particular interest is the positive association of gate opening with coparenting closeness and dyadic adjustment. Some work on maternal gate opening has suggested that gate opening may be destructive to the coparenting relationship because it could be viewed by fathers as maternal demandingness or nagging for increased father involvement (Fagan & Cherson, 2015). However, in Fagan and Cherson's study, maternal perceptions of facilitation of father involvement, which were associated with lower subsequent levels of father involvement, were reported by mothers, whereas mothers' encouragement of father involvement, which was associated with higher subsequent father involvement, was reported by fathers.…”
mentioning
confidence: 99%
“…Thus, the concept of maternal gatekeeping incorporates maternal behaviors that both inhibit and facilitate father involvement (Puhlman & Pasley, 2013; Schoppe-Sullivan, Brown, Cannon, Mangelsdorf, & Sokolowski, 2008). Early research on gatekeeping pertained primarily to married couples, and generally indicated that when mothers believe that fathers should be involved in child rearing, fathers tend to be more involved, but when mothers do not believe in the importance of father involvement, fathers tend to be less involved (Allen & Hawkins, 1999; Fagan & Cherson, 2017; Gaunt, 2008).…”
Section: Maternal Gatekeepingmentioning
confidence: 99%